Decisions for peace - "DeConde, Alexander." (New York)
Traces the events following the formation of the Federal Government in 1789 concentrating on the emergence of a foreign policy.
Keywords: UNITED STATES -- FOREIGN RELATIONS -- 1789-1809;-- JUVENILE LITERATURE.;UNITED STATES -- FOREIGN RELATIONS -- 1789-1809.